Inhibition of β-lactamase-mediated oxacillin resistance in Staphylococcus aureus by a deoxyribozyme - Hou Zheng; Meng Jing-ru; Zhao Jin-rong; Hu Ben-quan; Liu Jie; Yan Xiao-jun; Jia Min; Luo Xiao-xing (Acta Pharmacologica Sinica; Vol 28, No 11 (November 2007): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the oxacillin susceptibility restoration of methicillin-resistant Staphylococcus aureus (MRSA) by targeting the signaling pathway of blaR1-blaZ with a DNAzyme. Methods: A DNAzyme (named PS-DRz602) targeting blaR1 mRNA was designed and synthesized. After DRz602 was introduced into a MRSA strain WHO-2, the colony-forming units of WHO-2 on the Mueller-Hinton agar containing 6 mg/L oxacillin and the minimum inhibitory concentrations of oxacillin were determined. The inhibitory effects of DRz602 on the expressions of antibiotic-resistant gene blaR1 and its downstream gene blaZ were detected by real time RT-PCR. Results: PS-DRz602 significantly decreased the transcription of blaR1 mRNA and led to the significant reduction of blaZ in a concentration-dependent manner. Consequently, the resistance of S aureus WHO-2 to the β-lactam antibiotic oxacillin was significantly inhibited. Conclusion: Our results indicated that blocking the blaR1-blaZ signaling pathway via DNAzyme might provide a viable strategy for inhibiting the resistance of MRSA to β-lactam antibiotics and that BlaR1 might be a potential target for pharmacological agents combating MRSA.